Indicadores de mudanças nas práticas pedagógicas com o uso do computador portátil em escolas do Brasil e de Portugal - Weckelmann, Valéria Faria (2012)
The present investigation is linked to the programme of Post-Graduation in Education: Curriculum of the Pontificia Universidade Católica of São Paulo, (PUCSP), in the line of the research: New Technologies in Education . This study has, as principal objective to identify changes in the pedagogical practices of Professors, with the use of portable computers in the Brazilian and Portuguese Schools. It is searched to apprehend if the integration of the portable computer in the pedagogical practices implies in changes in the relationships between students and those with their teachers, if alterations would occur in the didactic strategies, as to identify the difficulties and contributions of the utilization of this movable device in education, seeking to find the necessary conditions so that the professors feel motivated and at ease to use this technology in their pedagogical practices. This refers to a qualitative research, to which a methodology is adopted of the research-action, beginning from the presumptions of Dewey, (1959), Sthenhouse, 1998, Elliott, (2000), and Zeichner,(2001), which developed in the process of a reciprocal collaboration between the researcher, professors and the students of the 4th year of the Portuguese and Brazilian Basic Education. For the collecting of information were adopted the following instruments registered in the newspaper of the Campo of the Researcher, questionnaire for the professors, interview semi-structured with the Professors and Students, collective interview projective and collective interview with the use of narratives with students. The analysis of the facts is based on the researches in the curriculum, of the reflexive pedagogical practices and of the integration of the curriculum and technologies, of the cooperation, Knowledge construction, of the cognitive tool and of the cycle of the actions and Spiral of the Apprenticeship. The study identifies changes in the pedagogical practices with the use of the portable computer in both contexts, as the reorganization of the management of time and of the space of the course, the horizontal part of the relationships between teachers and students, the perception of the error as the hypothesis of the reflection and the increasing of the motivation of the students. The changes evidenced in the Portuguese context were the development of the collaborative work and of the critical and reflexive thought , the initiative for the research, the digital inclusion of the families. The appearance of the digital vocabulary, the increasing of the Self-Esteem, the perception of the change of the role of the qualified personnel, motivation of the teachers, are specific changes in the Brazilian context. Identifies difficulties in both contexts as a lack of connection with the internet, need of the equipments of digital support as the interactive blackboard and multimedia projector and the fragility of the portable computer adopted. Points out difficulties in the Portuguese context as a lack of infrastructure of the local net, of the formation of the teachers and of the absence of the of the articulation between the political and administrative instances of the management of the school, and of the community, being specific difficulties of the Brazilian context, the slow operational system with the long navigation and the difficulties of the apprenticeship in the fundamentals of the Portuguese language and mathematics